Determination of the cross section for (n, p) and (n, α) reactions on 165Ho at 13.5 and 14.8 MeV. (April 2015) - Luo, Junhua; An, Li; Jiang, Li; He, Long
Abstract: Activation cross-sections for the 165 Ho(n, p) 165 Dy and 165 Ho(n, α) 162 Tb reactions were measured by means of the activation method at 13.5 and 14.8 MeV, to resolve inconsistencies in existing data. A neutron beam produced via the 3 H( d, n ) 4 He reaction was used. Statistical model calculations were performed using the nuclear-reaction codes EMPIRE-3.2 Malta and TALYS-1.6 with default parameters, at neutron energies varying from the reaction threshold to 20 MeV. Results are also discussed and compared with some corresponding values found in the literature. The calculational results on the 165 Ho(n, α) 162 Tb reaction agreed fairly well with experimental data, but there were large discrepancies in the results for the 165 Ho(n, p) 165 Dy reaction. Highlights: 27 Al(n, α) 24 Na was used as a monitor for neutron fleunce. The cross sections for the 165 Ho(n, p) 16 5 Dy and 165 Ho(n, α) 16 2 Tb reactions were measured at 13.5 and 14.8 MeV neutron energies. Nuclear reaction codes TALYS-1.6 and EMPIRE-3.2 Malta were used to model the reactions. Inconsistency with previous data and with model calculations are noted.